Study of the Use of Letter and Number Characters with Different Font Sizes in Running Text on Apparent Power - Sholahuddin wahid, M. Sholahuddin wahid; Ratna Mustika Yasi (Journal of Educational Engineering and Environment, 2023)
Technological advances make it easier to convey information in public places through media. LED displays are one of the information media that is widely used because they are more interesting to look at. This research focuses on the analysis of apparent power usage with variations in letter and number characters and differences in font size that occur in the running text when operated. Voltage and current testing uses analog and digital measuring instruments. The use of DC voltage that has been rectified from the output of the current sensor and voltage sensor is proportional to the current and the voltage is directly proportional to the voltage. Testing was carried out based on number and letter characters with font sizes of 15, 18 and 20 which were turned on for 10 minutes. Based on the research results, it shows that with different font sizes, letter and number characters have greater apparent power and resistance values as the font size increases, where the power value for letter characters is between 51-58 Volt Ampere, while for number characters it is between 49-58 Volt Ampere.